(untitled) - Long, Larry E. (Upper Saddle River, NJ., 1999)
Provides information to help students obtain competency with computers & aquire hands-on experience with computers. Paper. DLC: Computers.
Keywords: Electronic data processing,Xử lý dữ liệu điện tử